Genetic mapping studies of 40 loci and 23 cosmids in chromosome 11p13-11q13, and exclusion of mu-calpain as the multiple endocrine neoplasia type 1 gene. - Pang, J; Lloyd, SE; Wooding, C; Farren, B; Pottinger, B; Harding, B; Leigh, SE; Pook, M; Benham, F; Gillett, G; Taggart, RT; Thakker, R (1996)
Forty loci (16 polymorphic and 24 non-polymorphic) together with 23 cosmids isolated from a chromosome 11-specific library were used to construct a detailed genetic map of 11p13-11q13. The map was constructed by using a panel of 13 somatic cell hybrids that sub-divided this region into 19 intervals, a meiotic mapping panel of 33 multiple endocrine neoplasia type 1 (MEN1) families (134 affected and 269 unaffected members) and a mitotic mapping panel that was used to identify loss of heterozygosity in 38 MEN1-associated tumours. The results defined the most likely order of the 16 loci as being: 11pter-D11S871-(D11S288, D11S149)-11cen-CNTF-PGA-ROM1-D11S480-PYGM- SEA-D11S913-D11S970-D11S97- D11S146-INT2-D11S971-D11S533-11qter. The meiotic mapping studies indicated that the most likely location of the MEN1 gene was in the interval flanked by PYGM and D11S97, and the results of mitotic mapping suggested a possible location of the MEN1 gene telomeric to SEA. Mapping studies of the gene encoding mu-calpain (CAPN1) located CAPN1 to 11q13 and in the vicinity of the MEN1 locus. However, mutational analysis studies did not detect any germ-line CAPN1 DNA sequence abnormalities in 47 unrelated MEN1 patients and the results therefore exclude CAPN1 as the MEN1 gene. The detailed genetic map that has been constructed of the 11p13-11q13 region should facilitate the construction of a physical map and the identification of candidate genes for disease loci mapped to this region.